Token Constitutionalism and Islamic Opposition in Tajikistan - Atkin, Muriel (Journal of Persianate studies, 2012)
Abstract Tajikistan is a predominantly Muslim country where the concept of having a constitution is not controversial, but the content of that constitution is. Roughly seventy years of Soviet rule over the territory that became independent Tajikistan at the end of 1991 introduced constitutions as a norm, although the rights the constitutions appeared to accord did not jibe with political reality. The years of Soviet rule also created an environment hostile to Islam, as a result of which some of Tajikistan’s inhabitants ceased to be believers, while many who continued to practice their faith knew little about it other than the rituals of everyday life. In the last years of the Soviet era and the two decades after the breakup of the USSR, Islam was caught up in the political as well as religious controversies that developed in Tajikistan during this upheaval. There was an upsurge of attention to Islam, in a religious sense for some, a cultural and nationalist sense for others, and as a bogeyman for yet others. The Islamic Rebirth Party of Tajikistan (IRPT), the only legal Islamic political party in post-Soviet Central Asia, along with the head of the religious establishment in the republic, the qadi, joined with secular groups advocating reforms that would promote political and economic change. The power struggle between neo-Soviet ruling elites and the opposition led to a civil war (1992-97) in which the neo-Soviets prevailed. Tajikistan’s post-Soviet constitution reflects the emphatic secularism of the neo-Soviets, despite the objections of the IRPT. The post-civil-war government has also enacted legislation reestablishing Soviet-style constraints on Islamic institutions and personnel and has used its power to thwart genuinely pluralistic politics. The IRPT as well as secular opposition parties have felt the effects of the rigged elections and harassment by the regime.